Determination of Vitamin C (Ascorbic Acid) Using High Performance Liquid Chromatography Coupled with Electrochemical Detection - Gazdik, Zbynek; Zitka, Ondrej; Petrlova, Jitka; Adam, Vojtech; Zehnalek, Josef; Horna, Ales; Reznicek, Vojtech; Beklova, Miroslava; Kizek, Rene (Sensors (Basel, Switzerland), 2008)
Vitamin C (ascorbic acid, ascorbate, AA) is a water soluble organic compound that participates in many biological processes. The main aim of this paper was to utilize two electrochemical detectors (amperometric - Coulouchem III and coulometric - CoulArray) coupled with flow injection analysis for the detection of ascorbic acid. Primarily, we optimized the experimental conditions. The optimized conditions were as follows: detector potential 100 mV, temperature 25 °C, mobile phase 0.09% TFA:ACN, 3:97 (v/v) and flow rate 0.13 mL·min-1. The tangents of the calibration curves were 0.3788 for the coulometric method and 0.0136 for the amperometric one. The tangent of the calibration curve measured by the coulometric detector was almost 30 times higher than the tangent measured by the amperometric detector. Consequently, we coupled a CoulArray electrochemical detector with high performance liquid chromatography and estimated the detection limit for AA as 90 nM (450 fmol per 5 μL injection). The method was used for the determination of vitamin C in a pharmaceutical preparations (98 ± 2 mg per tablet), in oranges (Citrus aurantium) (varied from 30 to 56 mg/100 g fresh weight), in apples (Malus sp.) (varied from 11 to 19 mg/100 g fresh weight), and in human blood serum (varied from 38 to 78 μM). The recoveries were also determined.
Keywords: Electrochemical Detection; Pharmaceutical Preparation; Human Blood Serum; High Performance Liquid Chromatography; Fruits; Flow Injection Analysis; Ascorbic Acid